ENVIRONMENTAL PROTECTION UNDER THE LEGISLATION OF UKRAINE AND THE REPUBLIC OF POLAND: A COMPARATIVE ANALYSIS OF THE MAIN FEATURES - Artemenko Olena Viktorivna; Honcharuk Lidiya Yuriivna; Kachur Vira Olegivna; Lytvyn Nataliia Anatolyevna (Scientific Journal of Pedagogy and Economics, 2019)
Environmental protection plays an important role in the activities of each citizen individually and in the community as a whole. The article provides a comparative analysis of some aspects of environmental protection under the legislation of Ukraine and the Republic of Poland. The concept of environmental objects in the two countries studied is investigated. The main normative legal acts concerning the protection of the environment of Ukraine and the Republic of Poland are characterized. The main areas of focus on environmental protection are explored. The similarities between such spheres in Ukraine and the Republic of Poland are reflected. The necessity of the existence of bilateral agreements for both states to ensure co-operation and exchange of experience between the states has been proved. In the course of the study, it was found out that there is a close understanding of the main priorities of environmental protection activities in Ukraine and the Republic of Poland. The example of the Republic of Poland, as one of the Member States of the European Union, reflects the need to involve the experience of environmental law of the European Union. The necessity of the existence of three levels of institutional mechanism in the field of environmental protection: general, special and functional has been investigated. The main environmental protection measures that Ukraine will be able to implement in the coming years are identified, the main ones being: exchange of information and technologies, environmental monitoring, creation of a system of rational use of nature, exchange of experience in the field of improvement of management and legal regulation in the field of environmental protection improving the environmentally friendly waste storage and use system and others